Comparison of in-person versus tele-ultrasound point-of-care ultrasound training during the COVID-19 pandemic - Nilam J. Soni; Jeremy S. Boyd; Gregory Mints; Kevin C. Proud; Trevor P. Jensen; Gigi Liu; Benji K. Mathews; Christopher K. Schott; Linda Kurian; Charles M. LoPresti; Phil Andrus; Robert Nathanson; et al. (The Ultrasound Journal, 2021)
Abstract Background Lack of training is currently the most common barrier to implementation of point-of-care ultrasound (POCUS) use in clinical practice, and in-person POCUS continuing medical education (CME) courses have been paramount in improving this training gap. Due to travel restrictions and physical distancing requirements during the COVID-19 pandemic, most in-person POCUS training courses were cancelled. Though tele-ultrasound technology has existed for several years, use of tele-ultrasound technology to deliver hands-on training during a POCUS CME course has not been previously described. Methods We conducted a retrospective observational study comparing educational outcomes, course evaluations, and learner and faculty feedback from in-person versus tele-ultrasound POCUS courses. The same POCUS educational curriculum was delivered to learners by the two course formats. Data from the most recent pre-pandemic in-person course were compared to tele-ultrasound courses during the COVID-19 pandemic. Results Pre- and post-course knowledge test scores of learners from the in-person (n = 88) and tele-ultrasound course (n = 52) were compared. Though mean pre-course knowledge test scores were higher among learners of the tele-ultrasound versus in-person course (78% vs. 71%; p = 0.001), there was no significant difference in the post-course test scores between learners of the two course formats (89% vs. 87%; p = 0.069). Both learners and faculty rated the tele-ultrasound course highly (4.6–5.0 on a 5-point scale) for effectiveness of virtual lectures, tele-ultrasound hands-on scanning sessions, and course administration. Faculty generally expressed less satisfaction with their ability to engage with learners, troubleshoot image acquisition, and provide feedback during the tele-ultrasound course but felt learners completed the tele-ultrasound course with a better basic POCUS skillset. Conclusions Compared to a traditional in-person course, tele-ultrasound POCUS CME courses appeared to be as effective for improving POCUS knowledge post-course and fulfilling learning objectives. Our findings can serve as a roadmap for educators seeking guidance on development of a tele-ultrasound POCUS training course whose demand will likely persist beyond the COVID-19 pandemic.